TINJAUAN YURIDIS TERHADAP TINDAK PIDANA DESERSI YANG DILAKUKAN OLEH MILITER (STUDI KASUS PUTUSAN NOMOR 189-K/PMII-08/AU/XII/2021) - Eko Cahyono; Indah Kusuma Wardhani (Constitutum: Jurnal Ilmiah Hukum, 2024)
The crime of desertion is one of the offenses often found within military units. According to the 2022 report on law enforcement operations and military police justice, the disciplinary and code of conduct violations of TNI soldiers increased by 50% compared to 2021, and the crime of desertion also increased by 13.55%. Therefore, the author is interested in conducting research at Military Court II-08 Jakarta and analyzing Decision Number 189-K/PM.II-08/AU/XII/2021 related to the application of substantive criminal law and the judge's considerations in the trial of desertion crimes. The analysis based on this decision shows that the application of substantive criminal law to the crime of desertion committed by the Defendant in Decision Number 189-K/PM.II-08/AU/XII/2021 is appropriate, as it fulfills the elements of desertion in Article 87 paragraph (1) number 2 in conjunction with paragraph (2) of the Indonesian Military Penal Code (KUHPM). In this decision, the Panel of Judges has taken into account the legal facts, witness testimonies, supporting evidence, and the judge's conviction in rendering the verdict, thereby creating a deterrent effect on the Convict and instilling fear among military personnel to prevent them from committing the crime of desertion.